Law Enforcement on Criminal Acts of Abuse of Immigration Stay Permit on Foreign Citizens - Heri Immanuel Pratama; Jennifer Cecilia; Moch Agis Ali (LEGAL BRIEF, 2021)
The state of Indonesia is an archipelago that stretches from sabang to merauke with abundant wealth of natural resources and natural beauty, so this becomes a special attraction for foreign nationals to be able to enter Indonesia. Foreign nationals who want to enter Indonesia of course must go through immigration checkpoints for inspection, Immigration as an authorized agency to conduct checks and traffic control of people entering and exiting Indonesian territory based on the principle of selective (Selectif Policy) which only allows foreign nationals who provide benefits and do not endanger security or public order that is only allowed to enter and be able to be in Indonesia.However, not a few foreign nationals commit violations related to immigration in Indonesia such as by violating the deadline for residence permits (overstays) to misuse residence permits that are not in accordance with the purpose and purpose of the visa owned to carry out activities that are not in accordance with the rule of law in Indonesia such as working, smuggling, international crimes, and others. For this reason, law enforcement is in the form of granting immigration administrative actions to those who violate residence permits or law enforcement through projustisia judicial processes.